Gender at the heart of ICPD : the UNFPA strategic framework on gender mainstreaming and women's empowerment - Moser, Annalise (UNFPA New YorkUS, 2010)
Presents a new strategic framework on gender mainstreaming. Reflects lessons learnt from the 2008-2009 capacity assessment exercise. Also reflects the need for increased focus on gender in the context of addressing the goals of the International Conference on Population and Development (ICPD).